Extreme Levels of Air Pollution Associated With Changes in Biomarkers of Atherosclerotic Plaque Vulnerability and Thrombogenicity in Healthy Adults: The Beijing AIRCHD Study. Issue 5 (1st March 2019) - Xu, Hongbing; Wang, Tong; Liu, Shengcong; Brook, Robert D.; Feng, Baihuan; Zhao, Qian; Song, Xiaoming; Yi, Tieci; Chen, Jie; Zhang, Yi; Wang, Yang; Zheng, Lemin; et al.
Abstract : Rationale: : The pathophysiologic mechanisms of air pollution–associated exacerbation of cardiovascular events remain incompletely understood. Objective: : To assess whether ambient air pollution can be a trigger of the vulnerable plaque and heightened thrombogenicity through systemic inflammatory pathways. Methods and Results: : In Beijing AIRCHD study (Air Pollution and Cardiovascular Dysfunctions in Healthy Adults Living in Beijing), 73 healthy adults (mean±SD, 23.3±5.4 years) were followed up in 2014 to 2016. We estimated associations between air pollutants and biomarkers relevant to atherosclerotic plaque vulnerability, thrombogenicity, and inflammation using linear mixed-effects models and elucidated the biological pathways involved using mediation analyses. Receiver operating characteristic analyses were conducted to assess the ability of each biomarker to predict ambient air pollution exposures. High average concentrations of particulate matter in diameter <2.5 μm (91.8±63.8 µg/m 3 ) were observed during the study period. Significant increases in circulating biomarkers of plaque vulnerability, namely MMPs (matrix metalloproteinases; MMP-1, 2, 3, 7, 8, and 9), of 8.6% (95% CI, 0.1–17.8) to 141.4% (95% CI, 111.8–171.0) were associated with interquartile range increases in moving averages of particulate matter in diameter <2.5 μm, number concentrations of particles in sizes of 5 to 560 nm and black carbon, during the last 1 to 7 days before each participant's clinic visit. Higher air pollutant levels were also significantly associated with decreases in TIMP (tissue inhibitors of MMPs; TIMP-1 and 2), heightened thrombogenicity (shortened prothrombin time and increases in sCD40L [soluble CD40 ligand], sCD62P [soluble P-selectin], and fibrinogen/fibrin degradation products), and elevations in systemic inflammation (IL-1β [interleukin-1β], CRP [C-reactive protein], MIP-1α/β [macrophage inflammatory protein-1α/β], sRAGE [soluble receptor for advanced glycation end products], and IGFBP [insulin-like growth factor–binding protein]-1 and 3). Receiver operating characteristic curves showed that several biomarkers can serve as robust pollutant-specific predictors with high versus low black carbon exposure (area under the receiver operating characteristic curve of 0.974 [95% CI, 0.955–0.992] for MMP-8 and 0.962 [95% CI, 0.935–0.988] for sRAGE). Mediation analysis further showed that systemic inflammation can mediate ⩽46% of the changes in MMPs and thrombogenicity associated with interquartile range increases in air pollutants. Conclusions: : Our results suggest that air pollution may prompt cardiovascular events by triggering vulnerable plaque along with heightened thrombogenicity possibly through systemic inflammatory pathways. Abstract : Supplemental Digital Content is available in the text.